Vernacular Theology Dominican Sermons and Audience in Late Medieval Italy. - Corbari, Eliana (Berlin : De Gruyter, 2013)
This book examines the audiences and languages of Dominican sermons in late medieval Italy. It is a thorough analysis of how Latinate theological culture interacted with popular religious devotion. In particular it assesses the role of vernacular theology. Eliana Corbari defines vernacular theology as a form of theology that is based neither on a Latin scholastic model nor a monastic one. It is a "third dimension" of theology which was accessible to the laity, and in particular women, through their attendance at sermons and the reading of vernacular devotional works (in this case, medieval Ita.
Appendix D: Quantitative analysis of manuscripts examined in Chapter TwoBibliography; Index
Description based upon print version of record.
Keywords: Catholic Church -- Sermons; Dominicans -- Italy -- History -- To 1500.; Preaching -- Italy -- History -- To 1500.; Sermons, Medieval; Sermons; Dominicans -- Italy -- History; Sermons, Latin -- Italy -- History; Sermons, Italian -- History; Theology -- Italy -- History; Italy -- Church history -- 476-1400.; RELIGION / Christian Ministry / Preaching; Electronic books